1988
DOI: 10.1210/endo-123-5-2291
|View full text |Cite
|
Sign up to set email alerts
|

Triiodothyronine Exerts Direct Cell-Specific Regulation of Thyrotropin-Releasing Hormone Gene Expression in the Hypothalamic Paraventricular Nucleus*

Abstract: Thyroid hormone administered systemically exerts negative feedback control of biosynthesis of the TRH pro-hormone in the hypothalamic paraventricular nucleus (PVN), the origin of neurons that regulate anterior pituitary TSH secretion, but not in any other group of TRH-synthesizing neurons in the brain. To determine whether this response is mediated by direct effects on PVN neurons, we studied the effect of unilateral stereotaxic implants of L-T3 into the anterior hypothalamus on the concentration of pro-TRH mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(47 citation statements)
references
References 36 publications
1
43
1
Order By: Relevance
“…However, paraffin embedding interferes with RNA quality, thus better signal-to-noise ratio and analysis of gene expression are obtained using fixed frozen tissue. For example, in situ hybridization has been used to define TRH as a negatively T 3 -regulated gene in the hypothalamus (486)(487)(488)(489) and to study the cortex/dentate gyrus expression of RC3/neurogranin, which is positively regulated by T 3 (396).…”
Section: And Recommendation 43mentioning
confidence: 99%
See 1 more Smart Citation
“…However, paraffin embedding interferes with RNA quality, thus better signal-to-noise ratio and analysis of gene expression are obtained using fixed frozen tissue. For example, in situ hybridization has been used to define TRH as a negatively T 3 -regulated gene in the hypothalamus (486)(487)(488)(489) and to study the cortex/dentate gyrus expression of RC3/neurogranin, which is positively regulated by T 3 (396).…”
Section: And Recommendation 43mentioning
confidence: 99%
“…A related approach is to implant T 3 crystals stereotaxically into discrete hypothalamic areas. This method has been used to define the direct role played by T 3 in the TRH negative feedback mechanism (487,488) and to study the photoperiod-mediated regulation of seasonal energy balance and reproduction in the Siberian hamster (517). Furthermore, the direct role played by a number of neuropeptides on the HPT axis has been studied using the ICV route; for example, aMHS, neuropeptide-Y, and agouti-related protein (518)(519)(520)(521)(522).…”
Section: And Recommendation 44amentioning
confidence: 99%
“…Every fourth section of the PV N was hybridized with a 1241 base pair single-stranded 35 S-UTP-labeled cRNA probe for pro-TRH as described previously (Dyess et al, 1988;Kakucska et al, 1992). Serial sections taken from the arcuate nucleus were hybridized with a labeled 260 base pair single-stranded antisense 35 S-UTP RNA probe for AGRP, generously provided by Dr. G. Barsh (Stanford University School of Medicine, Stanford, CA) and previously characterized by Ollmann et al (1997).…”
Section: Light Microscopic Double-labeling Immunoc Ytochemistr Y Of ␣mentioning
confidence: 99%
“…We did not observe any change in Trh mRNA expression measured by qPCR in a punch of the PVN region 28 days after placement of T 3 Ps. A previous study using a hypothyroid rat model showed that unilateral T 3 crystalline implants within the anterior hypothalamus induced a marked reduction of Trh mRNA only in the medial parvocellular division of PVN as shown by in situ hybridization within 4 days (Dyess et al 1988). Moreover, a study by Murphy et al (2012) showed a mild suppression of hypothalamic Trh mRNA assessed by in situ hybridization 6 weeks after T 3 implants in the hypothalamus of Siberian hamsters.…”
Section: Discussionmentioning
confidence: 92%